Analisis Empiris Agresivitas Penghindaran Pajak Dalam Konteks Tanggung Jawab Sosial Perusahaan Dan Tata Kelola Perusahaan - Nurdiyani, Rachma Marta; Junaidi, Junaidi; Bawono, Icuk Rangga; Suparmono, Suparmono (E-Jurnal Akuntansi, 2025)
The issue of tax avoidance remains intriguing for further investigation in empirical studies. This research was conducted to re-examine the influence of corporate social responsibility and corporate governance on aggressive practices in tax evasion. The data source is from manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange between 2017 and 2021. This research used 168 companies with a purposive sampling method. Data analysis uses multiple linear regression using statistical software for social sciences. The research results show that the variables of corporate social responsibility, the presence of independent commissioners, and institutional ownership have a significant negative impact on aggressive practices in tax evasion. On the other hand, there is no significant influence of the audit quality variable on tax evasion. Therefore, the higher the level of corporate social responsibility disclosure, the proportion of the presence of an independent board of commissioners, the quality of audits, and the proportion of institutional ownership, the level of aggressive practices in tax evasion tends to decrease.  Keywords: Tax Avoidance; Social Responsibility; Ownership, Audit